Internet Addiction Disorder: Personality characteristics and risk of pathological overuse in adolescents - Munno, Donato; Cappellin, Flora; Saroldi, Marta; Bechon, Elisa; Guglielmucci, Fanny; Passera, Roberto; Zullo, Giuseppina (Psychiatry research, 2017)
Few studies have investigated Internet Addiction (IA) in adolescents in relation to personality characteristics. The aim of this study was to determine whether personality differences exist between adolescents with problematic/pathological Internet use and those with normal Internet use. Our hypothesis was that certain psychopathological personality traits may predispose to the development of maladaptive Internet use. The Internet Addiction Test (IAT) and the Minnesota Multiphasic Personality Inventory-Adolescent (MMPI-A) were administered to a sample of 224 high school students. Analysis of IAT scores showed that 24.6% of the students had problematic Internet use and 1.6% had IA. Comparison of the MMPI-A scores between subjects with normal Internet use and those with problematic or pathological use based on the IAT score showed that some subscales, including schizophrenia and bizarre mentation, were strongly associated with problematic/pathological Internet use. Also, male sex, attending a vocational school, and unhappy childhood were found to be risk factors for IA. Certain psychological dimensions regarding mood and the psychotic area, as well as low self-esteem, family, school and conduct problems could represent risk factors. Taken together, our data suggest a personality profile, with problems at various levels in subjects with problematic or pathological Internet use. •The prevalence of pathological and problematic Internet use is 1.6% and 24.6%, respectively.•Some personality traits may predispose to problematic/pathological Internet use.•Male sex and attending a vocational school are predictors of Internet Addiction.•High scores on the Schizophrenia scale of the MMPI-A may predict Internet Addiction.